Preparation method of solid-state lithium battery

By adopting polyion liquid-based solid electrolytes and combining the use of specific additives, the problem of narrow electrochemical window of polymer electrolytes is solved, and a solid lithium battery with high energy density and high safety is achieved.

CN119786711APending Publication Date: 2025-04-08SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411791642.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The narrow electrochemical window and ion transport mechanism of polymer electrolytes limit their application in high-energy density solid-state lithium batteries, especially challenges such as low ion conductivity in room temperature and polymer degradation at interfaces.

Method used

A polyion liquid-based solid electrolyte is used to form a polyion liquid-based solid electrolyte by mixing PDADMATFSI, additives and LiTFSI and then coating it on the substrate to form a polyion liquid-based solid electrolyte to construct a solid lithium battery. The additive is selected from the group consisting of LiDFOB, LiBODFP, LiBOB, TPFPB, TPFPP, THFPB and TP.

Benefits of technology

It realizes a wide electrochemical window, high lithium ion conductivity and high lithium ion migration number, improves the compatibility and electrochemical stability of high voltage positive electrode materials and low voltage negative electrode materials, and improves the energy density and safety of solid-state lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786711A_ABST
    Figure CN119786711A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a solid-state lithium battery. The preparation method comprises the following steps: providing PDADMATFSI; pDADMATFSI, an additive and LiTFSI are mixed and then coated on a substrate to form the polyion liquid-based solid electrolyte, and the additive is selected from at least one of the following substances: LiDFOB, LiBODFP, LiBOB, TPFPB, TPFPP, THFPB and TP; the solid-state lithium battery is constructed through the polyion liquid-based solid-state electrolyte. According to the preparation method of the solid-state lithium battery, the polyion liquid-based solid-state electrolyte which is non-combustible, good in processability, high in flexibility and ideal in chemical and electrochemical stability is adopted, so that the solid-state lithium battery has a wide electrochemical window, high lithium ion conductivity and high lithium ion transference number, is higher in interface contact with positive and negative electrode materials, and is small in interface impedance; the compatibility and the electrochemical stability of a high-voltage positive electrode material and a low-voltage negative electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium secondary battery, and more particularly to a method for preparing a solid-state lithium battery. Background Art

[0002] Lithium batteries dominate the power battery market due to their high energy density and cycle performance. However, with the rapid development of electric vehicles, existing lithium batteries can no longer meet the growing energy demand. Therefore, people have begun to pay extensive attention to lithium metal batteries composed of lithium metal anodes and high-voltage nickel-rich layered cathodes.

[0003] In the lithium battery system of liquid electrolyte, high energy density cathode materials are often accompanied by problems such as poor thermal stability and thermal runaway, which makes it difficult for them to meet the safety requirements of battery operation. In contrast, solid electrolytes show high adaptability to high energy density cathode materials due to their good thermal stability, electrochemical stability and mechanical properties. Therefore, solid-state lithium batteries have attracted much attention because they can achieve higher energy density while ensuring battery safety. As one of the core materials of solid-state batteries, solid electrolytes have a decisive influence on battery performance. The development of solid electrolytes with excellent performance is crucial to improving the performance of solid-state batteries.

[0004] Solid electrolytes are mainly divided into two types: inorganic solid electrolytes and polymer solid electrolytes. Inorganic solid electrolytes have good thermal stability and ionic conductivity, but their greater rigidity leads to poor solid-solid interface contact and large interface impedance. Polymer electrolytes can alleviate interface problems to a certain extent due to their easy processing and good flexibility. Therefore, among many solid electrolyte materials, organic polymer electrolytes have become an important direction for the development of solid-state batteries due to their excellent processability, flexibility and low cost.

[0005] However, the narrow electrochemical window and ion transport mechanism of polymer electrolytes limit their application in high energy density solid-state lithium batteries. In particular, challenges such as low room temperature ionic conductivity and polymer degradation at the interface limit their practical application in solid-state lithium batteries. Summary of the invention

[0006] In order to solve the above-mentioned problems of narrow electrochemical window of polymer electrolytes in the prior art, the present invention provides a method for preparing a solid-state lithium battery.

[0007] According to the method for preparing a solid-state lithium battery of the present invention, it comprises the following steps: S1, providing PDADMATFSI; S2, coating the mixed PDADMATFSI, an additive and LiTFSI on a substrate to form a polyionic liquid-based solid electrolyte, wherein the additive is selected from at least one of the following substances: LiDFOB, LiBODFP, LiBOB, TPFPB, TPFPP, THFPB and TP; and S3, constructing a solid-state lithium battery through the polyionic liquid-based solid electrolyte.

[0008] In a preferred embodiment, the mass of the additive is 1%-4% of the total mass of the polyionic liquid-based solid electrolyte.

[0009] In a preferred embodiment, the additive is 1%-3% LIDFOB and / or 1%-3% TPFPB.

[0010] In a preferred embodiment, the substrate is a PI film.

[0011] In a preferred embodiment, step S2 comprises: adding additives to PDADMATFSI, stirring for 10 min-1 h, then adding LiTFSI, continuing stirring for 1 h-24 h, applying the stirred solution on a substrate, and drying to obtain a polyionic liquid-based solid electrolyte.

[0012] In a preferred embodiment, after the coating, vacuum drying is performed at 50-70° C. for 12-36 hours to obtain a polyionic liquid-based solid electrolyte.

[0013] In a preferred embodiment, the positive electrode of the solid-state lithium battery is a nickel-rich layered oxide (LiNi x Mn y Co z O2, x+y+z=1, x>60%) or LiCoO2.

[0014] In a preferred embodiment, the negative electrode of the solid-state lithium battery is Li metal, Si, Sn or graphite.

[0015] In a preferred embodiment, the electrochemical window of the polyionic liquid-based solid electrolyte is 0-4.8V vs. Li / Li + .

[0016] In a preferred embodiment, the lithium ion conductivity of the polyionic liquid-based solid electrolyte is between 4.63×10 -4 ~6.41×10 -4 S / cm, and the lithium ion migration number is between 0.32 and 0.48.

[0017] According to the preparation method of the solid-state lithium battery of the present invention, a polyionic liquid-based solid electrolyte is used which is non-flammable, has good processability, high flexibility, and ideal chemical and electrochemical stability. It has a wide electrochemical window, high lithium ion conductivity, and high lithium ion migration number. It has higher interface contact with positive and negative electrode materials and small interface impedance, and can improve the compatibility and electrochemical stability of high-voltage positive electrode materials and low-voltage negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The charge and discharge curve (1C rate) of the Ll||PDADMATFSI+LiTFSI+1%LID FOB+3%TPFPB||NCM622 solid-state battery according to Example 8 of the present invention is shown. DETAILED DESCRIPTION

[0019] The preferred embodiments of the present invention are given below in conjunction with the accompanying drawings and described in detail.

[0020] The preparation method of the solid-state lithium battery according to the present invention first comprises providing polydimethyldiallylammonium bis(trifluoromethylsulfonyl)imide (PDADMATFSI). In a preferred embodiment, PDADMATFSI is synthesized by an ion exchange method.

[0021] The preparation method of the solid-state lithium battery according to the present invention then includes mixing PDADMATFSI, additives and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and coating the mixture on a substrate to form a polyionic liquid-based solid electrolyte. In a preferred embodiment, the additive is added to PDADMATFSI, stirred for 10 min-1 h, and then LiTFSI is added, and the stirring is continued for 1 h-24 h. The stirred solution is scraped on the substrate and dried to obtain a polyionic liquid-based solid electrolyte.

[0022] In a preferred embodiment, the additive is selected from at least one of the following substances: lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate (LiBODFP), lithium bisoxalatoborate (LiBOB), tris(pentafluorophenylborane) (TPFPB), tris(pentafluorophenyl)phosphine (TPFPP), tris(hexafluoroisopropyl) borate (THFPB), tris(2,2,3,3,3-pentafluoropropyl)borane (TP), etc. In a preferred embodiment, the additive is LIDFOB and / or TPFPB.

[0023] In a preferred embodiment, the mass of the additive is 1%-4% of the total mass of the polyionic liquid-based solid electrolyte. In a preferred embodiment, the additive is 1%-3% LIDFOB. In a preferred embodiment, the additive is 1%-3% TPFPB. In a preferred embodiment, the additive is 1%-3% LIDFOB and 1%-3% TPFPB.

[0024] In a preferred embodiment, the substrate is a polyimide film (PI film). In a preferred embodiment, the coating thickness is 150-250 um. In a preferred embodiment, after coating, vacuum drying is performed at 50-70° C. for 12-36 hours to obtain a polyionic liquid-based solid electrolyte.

[0025] The preparation method of the solid-state lithium battery according to the present invention finally comprises constructing a solid-state lithium battery by a polyionic liquid-based solid electrolyte. In a preferred embodiment, the positive electrode of the solid-state lithium battery is a high-voltage nickel-rich layered oxide or a high-voltage lithium cobalt oxide (LiCoO2). In a preferred embodiment, the positive electrode is a ternary material LiNi x Co y Mn z O2, x is greater than 60%, x+y+z=1, such as NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2). In a preferred embodiment, the negative electrode of the solid-state lithium battery is Li metal, Si (silicon), Sn (tin) or graphite. In a preferred embodiment, the solid-state lithium battery Li||NCM622 exhibits good electrochemical performance.

[0026] In the present invention, the additive has the advantages of a higher highest occupied molecular orbital (HOMO) energy level and a lower lowest unoccupied molecular orbital (LUMO) energy level. It is preferentially oxidized or reduced to form a cathode electrolyte interface (Cathode Electrolyte Interphase, CEI) and anode solid electrolyte interface (Solid Electrolyte Interphase, SEI) protective layer during the charge and discharge process of the solid-state lithium battery. The interface is stabilized by preventing direct contact between the polyionic liquid-based solid electrolyte and the electrode, thereby improving the stability of the electrode / electrolyte interface, effectively reducing or even eliminating the side reactions between the polyionic liquid-based solid electrolyte and the electrode interface under high voltage, thereby enhancing the stability of the polyionic liquid-based solid electrolyte under high voltage, increasing the battery operating voltage, allowing the battery to be charged at high voltage, and thereby improving the energy density of the solid-state battery. In a preferred embodiment, the polyionic liquid-based solid electrolyte has a very wide voltage window, relative to the lithium metal electrode (Li / Li + The voltage range for the standard potential of Li / Li is between 0 and 4.8 V. The electrochemical window of conventional polymer solid electrolytes is 0-4.3 V vs. Li / Li +, the upper limit of the charging voltage is only 4.3V. Electrochemical oxidation will occur under high voltage. Improving the surface stability by coating materials such as carbon-based materials and metal oxides will lead to side reactions and reduced energy density. In contrast, the upper limit of the charging voltage of the polyionic liquid-based solid electrolyte of the present invention is at least 4.5V, for example, the voltage window is 0-4.5V vs. Li / Li + , 0~4.6V vs.Li / Li + , 0~4.7V vs.Li / Li + No additional coating is required to improve surface stability, the process is simple and has a high safety factor.

[0027] In the present invention, the additive can improve the lithium ion conductivity of the polyionic liquid-based solid electrolyte and improve the charge and discharge performance of the solid-state lithium battery. For example, TPFPB can effectively inhibit the movement of TFSI anions, promote the movement of lithium ions, and thus improve the lithium ion conductivity. In a preferred embodiment, the polyionic liquid-based solid electrolyte has a high lithium ion conductivity of 4.63×10 -4 ~6.41×10 -4 S / cm, with a high lithium ion transference number between 0.32 and 0.48. Compared with the 1×10 -4 S / cm, the lithium ion conductivity of the polyionic liquid-based solid electrolyte of the present invention may be not less than 5.4×10 -4 S / cm, for example, between 5.41×10 -4 ~6.41×10 -4 In a preferred embodiment, the lithium ion transference number of the polyionic liquid-based solid electrolyte is between 0.40 and 0.48.

[0028] In summary, the polyionic liquid-based solid electrolyte according to the present invention has both a wide electrochemical window and high lithium ion conductivity, and is well compatible with high-voltage positive electrode materials and lithium metal negative electrode materials. The constructed lithium-ion battery has high discharge voltage, high energy density, high safety, low cost and good electrochemical performance.

[0029] Example 1

[0030] The process of synthesizing polyionic liquid PDADMATFSI by ion exchange method is as follows: weigh 20g 20wt.% polydimethyldiallylammonium chloride (PDADMACl) aqueous solution and mix and dilute with 100mL deionized water to make solution A. Dissolve 8.52g LiTFSI in 20mL deionized water to make solution B. Under stirring conditions, add solution B dropwise to solution A to generate a white precipitate, which is mixed to form solution C. After two hours of stirring, filter solution C, and then wash the collected precipitate. The washing time is not less than 0.5 hours, and the number of washings is not less than 5 times. The washed product is placed in a 90℃ blast oven for 2 hours, and then transferred to a 105℃ vacuum drying oven for further drying for 24 hours. After drying, take out the product and grind it into powder, and then place the powder sample in a 105℃ vacuum drying oven for 24 hours to obtain a pure white powder.

[0031] The process of making a polyionic liquid-based solid electrolyte is as follows: weigh 0.3g PDADMATFSI, add 1% LIDFOB and 0% TPFPB additives, stir for half an hour, then add 0.3g LiTFSI, and continue stirring for more than ten hours. Then apply the stirred solution on the PI film with a thickness of 200um. Put the film after the application into a vacuum drying oven at 60℃ and dry it for 24h to obtain a polyionic liquid-based solid electrolyte.

[0032] By constructing a Li||Li symmetric battery, electrochemical tests including linear sweep voltammetry and electrochemical impedance spectroscopy showed that its voltage window is 0-4.8V vs.Li / Li + , lithium ion conductivity 5.06×10 -4 S / cm, and the lithium ion transference number is 0.32.

[0033] Example 2

[0034] The process of synthesizing polyionic liquid PDADMATFSI by ion exchange method is as follows: weigh 20g 20wt.% PDADMACl aqueous solution and mix and dilute with 100mL deionized water to make solution A. Dissolve 8.52g LiTFSI in 20mL deionized water to make solution B. Under stirring conditions, add solution B dropwise to solution A to generate a white precipitate, which is mixed to form solution C. After two hours of stirring, filter solution C, and then wash the collected precipitate. The washing time is not less than 0.5 hours, and the number of washings is not less than 5 times. The washed product is placed in a 90℃ blast oven for 2 hours, and then transferred to a 105℃ vacuum drying oven for further drying for 24 hours. After drying, take out the product and grind it into powder, and then place the powder sample in a 105℃ vacuum drying oven for 24 hours to obtain a pure white powder.

[0035] The process of making a polyionic liquid-based solid electrolyte is as follows: weigh 0.3g PDADMATFSI, add 2% LIDFOB and 0% TPFPB additives, stir for half an hour, then add 0.3g LiTFSI, and continue stirring for more than ten hours. Then apply the stirred solution on the PI film with a thickness of 200um. Put the film after the application into a vacuum drying oven at 60℃ and dry it for 24h to obtain a polyionic liquid-based solid electrolyte.

[0036] By constructing a Li||Li symmetric battery, the voltage window was found to be 0-4.7V vs.Li / Li through electrochemical tests including linear sweep voltammetry and electrochemical impedance spectroscopy. + , lithium ion conductivity 6.41×10 -4 S / cm, and the lithium ion transference number is 0.34.

[0037] Example 3

[0038] The process of synthesizing polyionic liquid PDADMATFSI by ion exchange method is as follows: weigh 20g 20wt.% PDADMACl aqueous solution and mix and dilute with 100mL deionized water to make solution A. Dissolve 8.52g LiTFSI in 20mL deionized water to make solution B. Under stirring conditions, add solution B dropwise to solution A to generate a white precipitate, which is mixed to form solution C. After two hours of stirring, filter solution C, and then wash the collected precipitate. The washing time is not less than 0.5 hours, and the number of washings is not less than 5 times. The washed product is placed in a 90℃ blast oven for 2 hours, and then transferred to a 105℃ vacuum drying oven for further drying for 24 hours. After drying, take out the product and grind it into powder, and then place the powder sample in a 105℃ vacuum drying oven for 24 hours to obtain a pure white powder.

[0039] The process of making a polyionic liquid-based solid electrolyte is as follows: weigh 0.3g PDADMATFSI, add 3% LIDFOB and 0% TPFPB additives, stir for half an hour, then add 0.3g LiTFSI, and continue stirring for more than ten hours. Then, the stirred solution is scraped on the PI film with a scraping thickness of 200um. The scraped film is placed in a 60°C vacuum drying oven and dried for 24 hours to obtain a polyionic liquid-based solid electrolyte.

[0040] By constructing a Li||Li symmetric battery, the voltage window was found to be 0-4.5V vs Li / Li through electrochemical tests including linear sweep voltammetry and electrochemical impedance spectroscopy. + , lithium ion conductivity 5.72×10 -4 S / cm, and the lithium ion transference number is 0.41.

[0041] Example 4

[0042] The process of synthesizing polyionic liquid PDADMATFSI by ion exchange method is as follows: weigh 20g 20wt.% PDADMACl aqueous solution and mix and dilute with 100mL deionized water to make solution A. Dissolve 8.52g LiTFSI in 20mL deionized water to make solution B. Under stirring conditions, add solution B dropwise to solution A to generate a white precipitate, which is mixed to form solution C. After two hours of stirring, filter solution C, and then wash the collected precipitate. The washing time is not less than 0.5 hours, and the number of washings is not less than 5 times. The washed product is placed in a 90℃ blast oven for 2 hours, and then transferred to a 105℃ vacuum drying oven for further drying for 24 hours. After drying, take out the product and grind it into powder, and then place the powder sample in a 105℃ vacuum drying oven for 24 hours to obtain a pure white powder.

[0043] The process of making a polyionic liquid-based solid electrolyte is as follows: weigh 0.3g PDADMATFSI, add 1% LIDFOB and 1% TPFPB additives, stir for half an hour, then add 0.3g LiTFSI, and continue stirring for more than ten hours. Then apply the stirred solution on the PI film with a thickness of 200um. Put the film after the application into a vacuum drying oven at 60℃ and dry it for 24h to obtain a polyionic liquid-based solid electrolyte.

[0044] By constructing a Li||Li symmetric battery, the voltage window was found to be 0-4.8VV vs.Li / Li through electrochemical tests including linear sweep voltammetry and electrochemical impedance spectroscopy. + , lithium ion conductivity 5.47×10 -4 S / cm, and the lithium ion transference number is 0.38.

[0045] Example 5

[0046] The process of synthesizing polyionic liquid PDADMATFSI by ion exchange method is as follows: weigh 20g 20wt.% PDADMACl aqueous solution and mix and dilute with 100mL deionized water to make solution A. Dissolve 8.52g LiTFSI in 20mL deionized water to make solution B. Under stirring conditions, add solution B dropwise to solution A to generate a white precipitate, which is mixed to form solution C. After two hours of stirring, filter solution C, and then wash the collected precipitate. The washing time is not less than 0.5 hours, and the number of washings is not less than 5 times. The washed product is placed in a 90℃ blast oven for 2 hours, and then transferred to a 105℃ vacuum drying oven for further drying for 24 hours. After drying, take out the product and grind it into powder, and then place the powder sample in a 105℃ vacuum drying oven for 24 hours to obtain a pure white powder.

[0047] The process of making a polyionic liquid-based solid electrolyte is as follows: weigh 0.3g PDADMATFSI, add 1% LIDFOB and 2% TPFPB additives, stir for half an hour, then add 0.3g LiTFSI, and continue stirring for more than ten hours. Then, the stirred solution is scraped on the PI film with a scraping thickness of 200um. The scraped film is placed in a 60°C vacuum drying oven and dried for 24 hours to obtain a polyionic liquid-based solid electrolyte.

[0048] By constructing a Li||Li symmetric battery, the voltage window was found to be 0-4.7VV vs.Li / Li through electrochemical tests including linear sweep voltammetry and electrochemical impedance spectroscopy. + , lithium ion conductivity 5.41×10 -4 S / cm, and the lithium ion transference number is 0.40.

[0049] Example 6

[0050] The process of synthesizing polyionic liquid PDADMATFSI by ion exchange method is as follows: weigh 20g 20wt.% PDADMACl aqueous solution and mix and dilute with 100mL deionized water to make solution A. Dissolve 8.52g LiTFSI in 20mL deionized water to make solution B. Under stirring conditions, add solution B dropwise to solution A to generate a white precipitate, which is mixed to form solution C. After two hours of stirring, filter solution C, and then wash the collected precipitate. The washing time is not less than 0.5 hours, and the number of washings is not less than 5 times. The washed product is placed in a 90℃ blast oven for 2 hours, and then transferred to a 105℃ vacuum drying oven for further drying for 24 hours. After drying, take out the product and grind it into powder, and then place the powder sample in a 105℃ vacuum drying oven for 24 hours to obtain a pure white powder.

[0051] The process of making a polyionic liquid-based solid electrolyte is as follows: weigh 0.3g PDADMATFSI, add 1% LIDFOB and 3% TPFPB additives, stir for half an hour, then add 0.3g LiTFSI, and continue stirring for more than ten hours. Then apply the stirred solution on the PI film with a thickness of 200um. Put the film after the application into a vacuum drying oven at 60℃ and dry it for 24h to obtain a polyionic liquid-based solid electrolyte.

[0052] By constructing a Li||Li symmetric battery, the voltage window was found to be 0-4.8V vs.Li / Li through electrochemical tests including linear sweep voltammetry and electrochemical impedance spectroscopy. + , lithium ion conductivity 5.58×10 -4 S / cm, and the lithium ion transference number is 0.43.

[0053] Example 7

[0054] The process of synthesizing polyionic liquid PDADMATFSI by ion exchange method is as follows: weigh 20g 20wt.% PDADMACl aqueous solution and mix and dilute with 100mL deionized water to make solution A. Dissolve 8.52g LiTFSI in 20mL deionized water to make solution B. Under stirring conditions, add solution B dropwise to solution A to generate a white precipitate, which is mixed to form solution C. After two hours of stirring, filter solution C, and then wash the collected precipitate. The washing time is not less than 0.5 hours, and the number of washings is not less than 5 times. The washed product is placed in a 90℃ blast oven for 2 hours, and then transferred to a 105℃ vacuum drying oven for further drying for 24 hours. After drying, take out the product and grind it into powder, and then place the powder sample in a 105℃ vacuum drying oven for 24 hours to obtain a pure white powder.

[0055] The process of making a polyionic liquid-based solid electrolyte is as follows: weigh 0.3g PDADMATFSI, add 3% TPFPB additive, stir for half an hour, then add 0.3g LiTFSI, and continue stirring for more than ten hours. Then, the stirred solution is scraped on the PI film with a scraping thickness of 200um. The scraped film is placed in a 60°C vacuum drying oven and dried for 24 hours to obtain a polyionic liquid-based solid electrolyte.

[0056] By constructing a Li||Li symmetric battery, the voltage window was found to be 0-4.6V vs.Li / Li through electrochemical tests including linear sweep voltammetry and electrochemical impedance spectroscopy. + , lithium ion conductivity 5.28×10 -4 S cm -1 , the lithium ion migration number is 0.48.

[0057] Example 8

[0058] In order to demonstrate the excellent electrochemical performance of the solid electrolyte material, the voltage window, lithium ion migration number, and ion conductivity were comprehensively considered, and the solid electrolyte constructed in Example 6 was used to match the commercial NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2) positive electrode materials (positive electrode materials include various positive electrode materials lithium iron phosphate, lithium cobalt oxide, etc.), Li metal negative electrode materials to build solid-state lithium metal batteries (negative electrode materials include various negative electrode materials Si, Sn, graphite, etc.). The charge and discharge curve is as follows Figure 1As shown, the ordinate represents voltage and the abscissa represents specific capacity. From the curve in the figure, it can be seen that the output voltage of the constructed solid-state lithium metal battery is greater than 4.6V, and it exhibits a reversible capacity of 166mAh / g at a 1C rate. After calculation, the energy density of the battery can theoretically be greater than 500Wh / kg, showing excellent electrochemical performance. In addition, the lithium secondary battery has a simple preparation process, low cost, good wide temperature performance and excellent safety.

[0059] Table 1 Voltage window, lithium ion conductivity, and lithium ion migration number of solid electrolytes with different additives

[0060] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. A method for preparing a solid-state lithium battery, characterized in that: The preparation method comprises the following steps: S1, provide PDADMATFSI; S2, mixing PDADMATFSI, an additive and LiTFSI and coating the mixture on a substrate to form a polyionic liquid-based solid electrolyte, wherein the additive is selected from at least one of the following substances: LiDFOB, LiBODFP, LiBOB, TPFPB, TPFPP, THFPB and TP; and S3, constructing a solid-state lithium battery using a polyionic liquid-based solid electrolyte.

2. The preparation method according to claim 1, characterized in that: The mass of the additive is 1%-4% of the total mass of the polyionic liquid-based solid electrolyte.

3. The preparation method according to claim 1, characterized in that: The additives are 1%-3% LIDFOB and / or 1%-3% TPFPB.

4. The preparation method according to claim 1, characterized in that: The substrate is PI film.

5. The preparation method according to claim 1, characterized in that: The step S2 comprises: adding additives to PDADMATFSI, stirring for 10 min-1 h, then adding LiTFSI, continuing to stir for 1 h-24 h, applying the stirred solution on the substrate by scraping, and drying to obtain a polyionic liquid-based solid electrolyte.

6. The preparation method according to claim 5, characterized in that: After the coating, the mixture was dried under vacuum at 50-70° C. for 12-36 h to obtain a polyionic liquid-based solid electrolyte.

7. The preparation method according to claim 1, characterized in that: The positive electrode of solid-state lithium batteries is nickel-rich layered oxide or LiCoO2.

8. The preparation method according to claim 1, characterized in that: The negative electrode of solid-state lithium battery is Li metal, Si, Sn or graphite.

9. The preparation method according to claim 1, characterized in that: The electrochemical window of polyionic liquid-based solid electrolyte is 0-4.8V vs.Li / Li + .

10. The preparation method according to claim 1, characterized in that: The lithium ion conductivity of polyionic liquid-based solid electrolytes is between 4.63×10 -4 ~6.41×10 -4 S / cm, and the lithium ion migration number is between 0.32 and 0.48.